An Integrated Supply Chain Management Based Nila Nirwarna (Oreochromis niloticus) Seed Market Institution - Atikah Nurhayati; Ayi Yustiati; Titin Herawati (Jurnal Perikanan Universitas Gadjah Mada, 2019)
West Java Province is one of the potential areas of freshwater fisheries resources development in Purwakarta District. The utilization of development resources is directed to achieve comparative advantage and competitive advantage as an effort to encourage the growth of regional economy. Purwakarta is one area that has the potential of the aquaculture potential to be developed. One type of aquaculture that has a high economic potential such as tilapia nirwarna fish (Oreochromis niloticus), but in the institutional aspects of marketing there are still constraints from producers to consumers. This research aims to analyze marketing institutional of Nila seed (Oreochromis niloticus) through Integrated Supply Chain Management approach. The type of data used in this research is primary and secondary data. The analytical tool used marketing channels and supply chain risk by testing the validity and reliability of data. The technique of taking respondents using snowball sampling with the number of respondents 30 consisting of suppliers of nirwarna tilapia fish breeders to nirwarna tilapia seed cultivators. Based on the results of the research concluded that the analysis of tilapia supply chain risk has a value of 1.0 means it has a high risk. Based on the research results of the aquaculture business in Purwakarta is divided into two types of business, namely the enlargement effort and fish hatchery business. The marketing institutional of tilapia nirwarna seeds through Integrated Supply Chain Management approach in Purwakarta district through hilirization of tilapia fishery through the stage of input production supply and downstream of tilapia fishery fishery through fish farm institution through production and distribution output stage.